2020
DOI: 10.5173/ceju.2020.0258
|View full text |Cite
|
Sign up to set email alerts
|

Effect of perioperative selective alpha-1 blockers in non-stented ureteroscopic laser lithotripsy for ureteric stones: a randomized controlled trial

Abstract: Introduction The aim of this studywas to assess the efficacy of perioperative alpha-1 blockers on improving the success rate and decreasing complications of non-stented ureteroscopic laser lithotripsy for ureteric stones. Material and methods A randomized control trial was conducted at two high volume urological centers from September 2017 to December 2018. We enrolled 150 patients with lower ureteric stones. They were randomly divided into two groups. Patients in group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…After adopting the Split Bregman algorithm, the quality of the obtained image will be significantly improved, and the information degree of the image will be guaranteed, and the pixel distribution will be uniform and have better contrast. Finally, simulation experiments verify the feasibility and effectiveness of the algorithm [ 16 ]. A new fidelity term model is proposed to process medical images in B-mode: …”
Section: Laser Lithotripsy and Nursing Methodsmentioning
confidence: 99%
“…After adopting the Split Bregman algorithm, the quality of the obtained image will be significantly improved, and the information degree of the image will be guaranteed, and the pixel distribution will be uniform and have better contrast. Finally, simulation experiments verify the feasibility and effectiveness of the algorithm [ 16 ]. A new fidelity term model is proposed to process medical images in B-mode: …”
Section: Laser Lithotripsy and Nursing Methodsmentioning
confidence: 99%
“…The systematic review identified 15 RCTs [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] with 1653 patients (844 alpha-blockers; 809 controls) included in the meta-analysis (Figure S1). Preoperative alpha-blocker therapy involved tamsulosin S2).…”
Section: Resultsmentioning
confidence: 99%
“…The systematic review identified 15 RCTs 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 with 1653 patients (844 alpha‐blockers; 809 controls) included in the meta‐analysis (Figure S1 ). Preoperative alpha‐blocker therapy involved tamsulosin (11 studies) or silodosin (four studies) administered over 1 to 56 days before URS (median 7 days).…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, there is a lack of studies demonstrating the effectiveness of silodosin in reducing ureteral wall injury during UAS insertion. According to the explanation, silodosin has the potential to be more effective than other alpha-blockers in dilating the ureter [17]. In the study conducted by Kim et al, it was found that premedication with silodosin resulted in reduced insertion force and decreased damage to the ureteral wall, even after 2-3 days of taking the medication.…”
Section: Discussionmentioning
confidence: 99%